The interplay between multisensory associative learning and IQ in children - Barutchu, A; Fifer, J; Shivdasani, M; Crewther, S; Paolini, A (Wiley, 2019)
This study assessed the developmental profile of unisensory and multisensory processes, and their contribution to children's intellectual abilities (8‐ and 11‐year olds, N = 38, compared to adults, N = 19) using a simple audiovisual detection task and three incidental associative learning tasks with different sensory signals: visual‐verbal with pseudowords, novel audiovisual, and visual‐visual. The level of immaturity throughout childhood was dependent on both, the sensory signal type and the task. Associative learning was significantly enhanced with verbal sounds, compared to novel audiovisual and unisensory visual learning. Visual‐verbal learning was also the best predictor of children's general intellectual abilities. The results demonstrate a separate developmental trajectory for visual and verbal multisensory processes and independent contributions to the development of cognitive abilities throughout childhood.